A prática do plantão psicológico na delegacia especializada de atendimento à mulher (DEAM): uma experiência a partir da acontecência do cuidado - Lima, Darlindo Ferreira de (2012)
The aim of the present study was to understand the purpose of the psychology on duty practice in the women-specialized police stations. The action was performed in Juazeiro-BA and in Petrolina-PE and it was related to the obligatory internship of Psychology from UNIVASF. In this study, the psychology on duty, as a modality of pedagogical practice, was seen by an existential phenomenological view. From a Gadaner’s hermeneutic methodological perspective (2002) and from a proposal analytical perspective by Critelli (1996), it was observed the experience of the psychological interventions, for eight months. The meetings were registered mainly in the logbook from seven Psicology students and their supervisor. Dialogues were performed, which allowed the understanding of how this practical modality works. It was observed that the psychology on duty is characterized by hearing, care and clinical interventions that are not seen as modern technics. It allows the access of the one who looks for the service in its ontic-ontologic dimension and their appropriations. It aims to co-create purpose/meaning spaces by using the language as a clearing where the care “acontecência” occurs. The psychology on duty as a space of change seems to add new ways to be in front of your self existance, consisting of another ethos from the condition of “be-there”.